Equity Education in Nepal - Basnet, Hom Bahadur; Raya, Hikmat Bahadur; Kattel, Balchandra; Thapa, Purna Bahadur (Journal of Research and Development, 2026)
This study explored issue of educational equity in l Nepal by employing a qualitative research methodology under an interpretive research paradigm. This qualitative study investigated the experiences, challenges, and opportunities associated with educational equity in four public primary schools of Chaubise Rural Municipality, located in the Dhankuta district of Nepal. Under an interpretive research paradigm, this study employed purposive sampling to select head teachers, classroom teachers, SMC members, and students from those schools. The study findings indicate that educational inequality in l Nepal is influenced by interrelated structural, social, linguistic, and institutional factors. Some of the significant challenges associated with educational inequality in l Nepal include poverty, geographical inaccessibility, infrastructural scarcity, poor governance, teachers’ training, caste-based discrimination, and linguistic barriers, particularly for students belonging to marginalized castes, ethnic groups, and linguistic communities. Similarly, this study revealed that Nepali/English-medium instruction may be a barrier for students who are mother-tongue speakers. Despite all these barriers, it was identified that schools possess certain significant strengths in their contexts too. Adaptive leadership, equity-oriented school practices, teachers' agency, mother tongue support, community engagement, and adaptive teaching strategies were identified to be having a significant role in the promotion of inclusive education and the encouragement of active participation. Teachers' professionalism and context-oriented practices may act as a bridge in bridging the gap between policy and practice. The study has shown that the achievement of equity in education in Nepal is not only dependent on the provisions of the policy but also on the provisions of responsive leadership and inclusive governance, culturally and linguistically sensitive education, institutional support, and the elimination of discrimination.